The Semiotics of Xenophobia and Misogyny on Digital Media: A Case Study in Spain - Römer-Pieretti, Max; Montero-Díaz, Julio; Said-Hung, Elías Manuel (IGI Global, 2024)
This chapter raises three questions: a) concerns a synthesis of the classic contributions of the reference semiotic authors that are considered when analysing hate speech in social media; b) entails presenting a case study that is analysed precisely with that analysis synthesis; c) shows the usefulness and interest of this type of analysis in investigations of hate speech. It offers a semiotic model for analysing misogynistic and xenophobic hate speech from digital news media on Twitter. The case study comprises the news published by El Mundo (Spain) from its users on social media, and the 33 comments generated, as a reason for this publication, during January 2021. This serves as the basis of semiotic analysis for understanding the phenomenon. The results visualise the semiotic analyses for understanding the dissemination of expressions. This approach thus helps reveal the levels of intensity, the denotative and connotative differences, the destructive-constructive and intertextual nature of messages, and sheds light on the different symbolic structures associated with hate speech.
Keywords: reference semiotic; social media; xenophobia; misogyny; digital media; Spain; España; xenofobia; misoginia; Scopus